Mobilizing for the Common Good : The Lived Theology of John M. Perkins - Heltzel, Peter; Marsh, Charles, 1958-; Slade, Peter, 1970- (Book collections on Project MUSE., 2013)
Born into a sharecropping family in New Hebron, Mississippi, in 1930, and only receiving a third-grade education, John M. Perkins has been a pioneering prophetic African American voice for reconciliation and social justice to America's white evangelical churches. Often an unwelcome voice and always a passionate, provocative clarion, Perkins persisted for forty years in bringing about the formation of the Christian Community Development Association--a large network of evangelical churches and community organizations working in America's poorest communities--and inspired the emerging generati.